I Saw You in the Bathtub: And Other Folk Rhymes - Alvin Schwartz (Cessnock, NSW, Australia Lioncrest Education Pty Ltd, 1991)
A collection of 41 folk rhymes, taunts, and insults that have been chanted, sung, and shouted by generations of children throughout the United States. 'Children will appreciate the humor of the rhymes and the illustrations. Another I Can Read hit.' --SLJ.
Keywords: Level Reader -- Level Reader